A comprehensive perspective of unreliable public transport services' costs. Issue 3 (1st January 2020) - Muñoz, Juan Carlos; Soza-Parra, Jaime; Raveau, Sebastián
Abstract : In recent decades, the main focus of public transport operations has been increasing its speed. Increasing speed not only allows for faster trips but also a higher frequency with the same fleet size, thus reducing waiting times and crowdedness inside the vehicles. This interest in speed has ignored a second key dimension in the level of service: reliability. In this article, we provide a review of a full range of impacts of an unreliable public transport service. We show how regularizing headway could improve level of service beyond the gains of simply increasing the operational speed. Regular headways positively affect comfort, reliability, travel and wait time, operational costs, and even some urban impacts of bus services. Thus, the focus for public transport agencies and operators should bend into reliability's direction. This is fundamental for making public transport an attractive travel alternative, and therefore must become a core goal for urban sustainability.